George M. Duck Lecture - Naqvi, Yasir (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2018)
The Hon. Yasir Naqvi, Attorney General of Ontario, delivered the George M. Duck Lecture at the University of Windsor Faculty of Law on February 28, 2018.